Development of a 3D Model of a Manipulator for Mobile Robotic Platforms Based on Unigraphics NX - Nevliudov, I.; Yevsieiev, V.; Demska, N.; Valkivskyi, Y. (Видавничий дім «Гельветика», 2022)
The article discusses the issues of modernization of the mobile robot Festo Robotino, due to the integration of the MR-999E manipulator system into it. This solution will significantly expand the functionality of the mobile robot Festo Robotino and will allow for new research related to the development of new methods and models for making decisions on moving objects. Based on the study, it was revealed that the existing MR-999E manipulator system has a number of disadvantages, one of which is the insufficient compression force of the gripper to move the test objects, which does not allow it to be widely implemented as a mobile manipulation platform. To eliminate these shortcomings, the authors carried out research, on the basis of which a kinematic diagram of the gripping module was developed. To check the correctness of the decisions made and the obtained calculations in the CAD Unigraphics NX system, 3D models of all the main elements of the mobile manipulator were developed, the dimensions of the teeth with an involute profile were calculated, which made it possible to increase the positioning accuracy of the links in space to solve the problem of spatial assembly of structures with the required accuracy. Based on the developed 3D models, the authors have designed a detailed 3D model of the manipulator assembly, in the CAD Unigraphics NX system, as well as using numerical engineering analysis, based on the finite element method, calculations were carried out to determine the required gripping force of the improved gripping mechanism. The developed 3D models are made using additive 3D printing technologies. This made it possible to manufacture a prototype of the gripping mechanism and experimentally confirm the possibility of integrating it with the Festo Robotino mobile robot in order to expand its functionality.
Keywords: mobile robots; Festo Robotino; mobile manipulators; 3D model; modeling